Facile synthesis of In2S3/UiO-66 composite with enhanced adsorption performance and photocatalytic activity for the removal of tetracycline under visible light irradiation - Dong, Wenbo (2021)
In this study, a series of In2S3/UiO-66 composites were fabricated through a one-step solvothermal method for the first time. The diffraction peaks, composition, morphology, and chemical states of the composites were first characterized through X-ray diffraction, X-ray photoelectron spectroscopy, scanning electron microscope, or transmission electron microscope. Then, the performances of as-obtained In2S3/UiO-66 composites were assessed by the removal of tetracycline under 1 h dark condition and 1 h visible-light irradiation. Experimental results showed that all the In2S3/UiO-66 composites exhibited greater tetracycline removal, as compared with the two parent materials (i.e., UiO-66 and In2S3). The highest tetracycline removal was obtained by the developed In2S3/UiO-66 composite with Zr: In molar ratio of (0.37:1), labelled as ISUO-0.37, with the maximal tetracycline removal capacity of 106.3 mg/g being achieved, which was greater than that of UiO-66, In2S3, or other photocatalysts documented in the literature. The mechanism investigations revealed that compared with UiO-66 and In2S3, ISUO-0.37 had higher adsorption capability and photocatalytic performance. Although the specific surface area of ISUO-0.37 (74.57 m2/g) was lower than that of either UiO-66 (388.6 m2/g) or In2S3 (76.36 m2/g), the former possessed greater pore diameter and adsorption sites such as single bondOH, Cdouble bondO, Osingle bondCsingle bondO, Cdouble bondC, and Csingle bondH, which might be the reason for ISUO-0.37 showing the enhanced adsorption capability. The trapping experiment and electron spin resonance measurements demonstrated that radical dotO2− and h+ were the major contributors to the photo-degradation of tetracycline in this work, and more radical dotO2− and h+ were produced by ISUO-0.37, as compared with In2S3. Further investigation with the diffused spectra of reflectance showed that ISUO-0.37 had better visible light absorption than either In2S3 or UiO-66, which may be the reason for ISUO-0.37 producing more radical dotO2−. In addition, photoluminescence emission spectra confirmed that the recombination rate of photoexcited electron-hole pairs of ISUO-0.37 composite is much lower than that of In2S3, which may increase h+. It was also found that ISUO-0.37 showed excellent structural stability and recyclability.